Primary headaches in obese patients Cefaléias primárias em pacientes obesos - Mario Fernando Prieto Peres; Daniel Diniz Gonçalves Lerário; Arthur Belarmino Garrido; Eliova Zukerman (Arquivos de Neuro-Psiquiatria, 2005)
BACKGROUND AND OBJECTIVE: Obesity is a major public health problem worldwide. Little is known about the prevalence and impact of headache disorders in obese patients. The objective of this study was to assess the prevalence of primary headaches in obese patients and controls. METHOD: Seventy-four consecutive obese patients from the obesity surgery service were studied, and compared to controls with body mass index less than 25. RESULTS: Fifty-six patients (75%) had a headache diagnosis, 49 migraine (66%), 7 tension-type headache (9%), 36 (48%) had incapacitating headaches. CONCLUSION: Primary headaches are more common and incapacitating in obese patients than controls, migraine is the most important diagnosis in this population. Headaches should be properly diagnosed and treated in obese patients. INTRODUÇÃO: Obesidade é um problema de saúde publica relevante em todo o mundo. Pouco se sabe sobre a prevalencia e impacto das cefaléias em pacientes obesos. OBJETIVO: Avaliar a prevalência de cefaléias primárias em pacientes obesos. MÉTODO: Setenta e quatro pacientes consecutivos originários de um centro de tratamento de obesidade foram estudados e comparados com controles com índices de massa corporal menores que 25. Resultados: Cinquenta e cinco pacientes (75%) apresentaram algum diagnóstico de cefaléia primária, 49 enxaqueca (66%), 7 cefaléia do tipo tensional (9%), 36 (48%) tiveram cefaléias incapacitantes. CONCLUSÃO: Cefaléias primárias são mais comuns e incapacitantes em pacientes obesos que controles, a enxaqueca é o diagnóstico mais freqüente nesta população. Cefaléias devem ser adequadamente diagnosticadas e tratadas em pacientes obesos.